249 Getting young people's rights right: paediatric dept staff survey on UN Convention on the Rights of the Child (UNCRC). (17th August 2022) - Srinivas, Jyothi; Williamson, Max; Curtis, Aisling
Abstract : Aims: We wished to explore the knowledge and awareness about 'Rights of a child' as mentioned in the UN convention among paediatric staff in a District General Hospital in the UK. The United Nations Convention on the Rights of the Child (UNCRC) is an international human rights treaty which sets out the civil, political, economic, social, health and cultural rights of children. The Convention defines a child as any human being under the age of eighteen, unless the age of majority is attained earlier under national legislation. Methods: An online survey was designed for staff in our paediatric department on their knowledge of the UNCRC. The survey was advertised in the department and we collected 36 responses between August and September 2021. Staff who completed the survey included trainee doctors, consultants, nurses, allied health care professionals and administrative staff. Results: A total of 36 responses were collected. Zero respondents reported being very familiar with UNCRC and 28% were unfamiliar about Childrens rights. 55% of staff correctly reported that the United States was the only member of the UN to have not ratified the UNCRC. 53% of staff correctly recognised the four General Principles of the Convention: Acting in the child's best interests; supporting the child's right to be heard; acting to support the child's right to life; and acting without discrimination. Importantly, 89% felt it would be useful to provide information on the UNCRC for staff, patients, and families. Staff suggested a range of methods, such as pamphlets, small-group teaching, and being a part of e-learning and safeguarding training, as ways of providing information about this topic. Conclusion: Protecting the rights of children and young people is an essential part of paediatrics. From our single-centre audit, it is concerning that staff knowledge on these rights and the UNCRC is lacking and can be variable. We are now designing infographics on UNCRC for staff and children in our department. This topic will be covered at medical and nursing induuction in our department going forward. We hope that this highlights a key area of supporting young people within our working environments. The UNCRC applies to all children, and its key messages should be woven into the wider work that we perform in paediatric departments across the UK.